Erdheim-Chester disease: consensus recommendations for evaluation, diagnosis, and treatment in the molecular era - Goyal, Gaurav; Heaney, Mark L; Collin, Matthew; Cohen-Aubart, Fleur; Vaglio, Augusto; Durham, Benjamin H; Hershkovitz-Rokah, Oshrat; Girschikofsky, Michael; Jacobsen, Eric D; Toyama, Kazuhiro; Goodman, Aaron M; Hendrie, Paul; et al. (Blood, 2020)
Erdheim-Chester disease (ECD) is a rare histiocytosis that was recently recognized as a neoplastic disorder owing to the discovery of recurrent activating MAPK (RAS-RAF-MEK-ERK) pathway mutations. Typical findings of ECD include central diabetes insipidus, restrictive pericarditis, perinephric fibrosis, and sclerotic bone lesions. The histopathologic diagnosis of ECD is often challenging due to nonspecific inflammatory and fibrotic findings on histopathologic review of tissue specimens. Additionally, the association of ECD with unusual tissue tropism and an insidious onset often results in diagnostic errors and delays. Most patients with ECD require treatment, except for a minority of patients with minimally symptomatic single-organ disease. The first ECD consensus guidelines were published in 2014 on behalf of the physicians and researchers within the Erdheim-Chester Disease Global Alliance. With the recent molecular discoveries and the approval of the first targeted therapy (vemurafenib) for BRAF-V600-mutant ECD, there is a need for updated clinical practice guidelines to optimize the diagnosis and treatment of this disease. This document presents consensus recommendations that resulted from the International Medical Symposia on ECD in 2017 and 2019. Herein, we include the guidelines for the clinical, laboratory, histologic, and radiographic evaluation of ECD patients along with treatment recommendations based on our clinical experience and review of literature in the molecular era.